Basic amenities, deficiency-induced ailments, and catastrophic health spending in the slums of Lucknow, Uttar Pradesh - Nayak, Sanatan and Jatav, Surendra Singh (Economic and Political Weekly)
The pattern of disease that comes about due to inadequate availability and poor quality of drinking water as well as substandard sanitation and micro-environmental (drainage, sewerage, and solid waste disposal) facilities in the slums of Lucknow are investigated in this paper. It estimates the relevant health costs and catastrophic health spending in these slum households. The results suggest that limitations in these public utilities cause numerous water-borne and faecal-transmitted infections as well as other infectious diseases. Consequently, the poorest sections of the urban population of Lucknow, who live in slums, spend almost a third of their consumption expenditure on out-of-pocket expenditure, and over half of these disease-affected households have encountered CHS. It suggests a comprehensive and integrated approach for reviving a large number of short- and long-term policies, which involve specifically developing a policy for providing free medical facilities to all acute and chronic cases in poor households, which would lead to a reduction of OOPE and CHS in slum areas.- Reproduced